Penurunan Temperatur Instalasi Kabel NYM 2x1.5mm2 Dengan Mengatur Sudut Penekukan - Mauludi Manfaluthy; Muhammad Syukur; Adi Supriyadi (Diponegoro University, 2018)
One of the major causes on high temperature of the cable wires are erroneous bent position. Apparently at certain circumstances such as home or factory, cable installation must not be applied in upright assemble. There is a considerable that the cable installation must be applied in bent position. It was found that imprudent cable bending installation more likely to cause higher temperature to the cable. Considering controversy surrounding higher heat may occur to smaller and taper bending angle cable when it is electrified, it was designed an innovative solution to demote the temperature of NYM 2 x 1,5mm2 cable installation by regulating the cable bent angle. In this research, NYM 2 x 1.5mm2 cable were used as insulation resistance test by flowing it with various electric current as well as 5A, 10A, 17A, 18A and 19A. Cable bending angle were tested at 30o, 60o, 90o, 120o , and behind-bent wires. The test equipment was Omicron CPC 100 which has the capabilities of driving the output voltage up to 2kV AC with electrical currents output up to 800A and 400A DC. The results were significant to the cable with mild bending angle that reduces the amount of temperature which stopped isolation from burning and prevented conductive wire from melting where taper bending cable angle with (300) isolation were likely to be more flammable.